Online Business Marketing Strategy in Terms of Discounts and Ease of Transactions on Purchasing Decisions - Suliawati, Silvia; Pristiyono, Pristiyono; Ihsan, Muhammad Ali Al (Almana : Jurnal Manajemen dan Bisnis, 2023)
A digital business strategy is a long-term plan designed to manage a business through the use of digital technology and the Internet. The goal is to maximize added value for customers. The purpose of this study is to determine the driving factors for purchasing decisions in digital business. In this case, the researcher wants to test the effect of price discounts and ease of transactions on purchasing decisions. The research approach used is quantitative research with the method used is the questionnaire method. The population was 100 respondents who owned and had purchased an online business for transactions. The sampling technique in this study was to use a total sampling technique. In this study researcher used a questionnaire that was filled out by respondents via the Google form to measure the results of the research variables. This study uses data analysis techniques using SmartPLS (Partial Least Square) software which is a variance-based structural equation analysis (SEM) that can simultaneously test structural models. The results showed that the discount variable had no significant effect on customer purchasing decisions in online business, then the transaction convenience variable proved to have a significant effect on online purchasing decisions in the community in Labuhanbatu Regency.